Fazenda Providência e Escola João Goulart: uma proposta de turismo pedagógico através de vivências e experiências no meio rural. - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work focuses on rural tourism through educational activities among children and adolescents, having as study field a farm and a school located in the municipality of Arroio Grande / RS. The objective of this work is to present a proposal for the development of pedagogical rural tourism in the Providencia Farm in Arroio Grande/RS, based on the valuation of the environment, rural man's contributions to the daily life of children and adolescents, as well as an opportunity to supplement the income of farmers and ranchers in the municipality. It was sought the participation of the Municipal School of Fundamental Education President João Goulart, that has in its school curriculum the discipline of Administration and Agriculture. This discipline seeks to involve rural activities as a teaching practice, in addition to dialogue with other disciplines of the curricular plan. In order to justify the study, the general aspects on rural tourism and pedagogical tourism, from bibliographic studies, were approached. As for the methodology, the research is characterized with qualitative approach, applied nature, descriptive objectives and bibliographic procedures, documentaries and case study. Data were collected from the owners of Fazenda Providência and one teacher from João Goulart School. With the results of the research it was possible to elaborate a proposal of pedagogical rural tourism and it was verified the viability of application in the Providence Farm, despite the necessity of some adaptations in the space. The practical activities carried out by the school in rural areas can help in understanding and training citizens who are more aware and critical about the issues presented to them.
Keywords: Turismo Rural; Turismo Pedagógico; Fazenda Providência; Escola João Goulart; Arroio Grande, RS; Rural Tourism; Pedagogical Tourism; Providence Farm; João Goulart School; Arroio Grande, RS; CNPQ::CIENCIAS SOCIAIS APLICADAS